Draft Annual Plan 1995-96 Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1995)
Coconut cultivation is central to the economy of the islands. There is great need to increase its yield through application of modern technology. Cottage and small scale industries based on coconut specially on coir need to be encouraged. Tourism is one of the sectors in Lakshadweep with great potential for development. Lakshadweep EEZ with an area of 4 lakhs Sq.Kms. is rich in its fishery resources. During the last two decades significant strides have been made in the development of fisheries. The annual catch which was less than 500 tonnes in 1960 has risen to 7600 tonnes.
Union Territory of Lakshadweep, Planning Cell